Combining spectral and texture feature of UAV image with plant height to improve LAI estimation of winter wheat at jointing stage - Zou, Mengxi; Liu, Yu; Fu, Maodong; Li, Cunjun; Zhou, Zixiang; Meng, Haoran; Xing, Enguang; Ren, Yanmin (Frontiers in Plant Science, 2024)
Leaf area index (LAI) is a critical physiological and biochemical parameter that profoundly affects vegetation growth. Accurately estimating the LAI for winter wheat during jointing stage is particularly important for monitoring wheat growth status and optimizing variable fertilization decisions.Taking Xixingdian Township,Cangzhou City,Hebei Province,China as the research area in this paper, and four machine learning algorithms,namely,support vector machine(SVM),back propagation neural network(BPNN),random forest(RF),extreme gradient boosting(XGBoost), and two deep learning algorithms,namely,convolutional neural network(CNN) and long short-term memory neural network(LSTM),were applied to estimate LAI of winter wheat at jointing stage by integrating the spectral and texture features as well as the plant height information from unmanned aerial vehicle(UAV) multispectral images.Initially,Digital Surface Model(DSM) and Digital Orthophoto Map(DOM) were generated. Subsequently, the plant height(PH),vegetation indices(VI) and texture features were extracted,and the texture indices(TI) was further constructed.The measured LAI on the ground were collected for the same period and calculated its Pearson correlation coefficient with PH,VI and TI to pick the feature variables with high correlation.The VI,TI,PH and fusion were considered as the independent features, and the sample set partitioning based on joint x-y distance (SPXY) method was used to divide the calibration set and validation set of samples.The ability of different inputs and algorithms to estimate winter wheat LAI were evaluated.The results showed that1) The addition of PH as a feature variable significantly improved the accuracy of the LAI estimation,indicating that wheat plant height played a vital role as a supplementary parameter for LAI inversion modeling based on traditional indices;2) The combination of texture features,including normalized difference texture indices(NDTI),difference texture indices(DTI), and ratio texture indices(RTI), substantially improved the correlation between texture features and LAI; Furthermore, multi-feature combinations of VI,TI, and PH exhibited superior capability in estimating LAI for winter wheat;3) Six regression algorithms have achieved high accuracy in estimating LAI,among which the XGBoost algorithm estimated winter wheat LAI with the highest overall accuracy and best results.This study provided compelling evidence that utilizing XGBoost and integrating spectral, texture,and plant height information extracted from UAV data can accurately monitor LAI during the jointing stage of winter wheat.